Impact of Certification System on Smallhold Coffee Farms’ Income Distribution in Vietnam - Nguyen , Thi Minh Chi; Chien , Li-Hsien; Chen , Shwu-En (Asian Journal of Agriculture and Rural Development, 2015)
This study attempts to investigate the impact of the working certification programs on the income of the coffee farms operated by the local smallholders at Dakha District, Kontum, Vietnam. Followed by the comparisons of the socio-demographic and economic characteristics between certified and non-certified farmers, the study adopts the Binary Probit model and linear regression model were applied to analyze the decision on farmers’ attitude for participation on the available certification programs and their impacts. Propensity score matching (PSM) was applied to examine the average treatment effect of certification program on net coffee income per hectare to reduce the selection bias. Statistical results show that net coffee income per hectare is positively influenced by certification participation. Furthermore, education status the household head, number of members involved in coffee cultivation, distance from household to town center, and training availability effect significantly on net coffee income. Moreover, four matching algorithms of PSM highlighted that members of the certified cooperative achieve higher net coffee income per hectare compared to non-certified ones. Finally, how to introduce an organizational framework to assist local smallhold farmers and local coffee cooperatives become more effective and influential in domestic coffee value chain are suggested.